Analisis Preferensi Konsumen Terhadap Pembelian Rangkaian Bunga Pada Toko Quinn Florist Di Kelurahan Winangun Dua Kecamatan Malalayang Kota Manado - Sulfiana; Maweikere, Audrey Julia Maria; Katiandagho, Theodora Maulina (AGRI-SOSIOEKONOMI, 2024)
The aim of the research is to analyze consumer preferences for purchasing flower arrangements at the Quinn Florist shop in Winangun Dua Village, Malalayang District, Manado City. This research lasted for six months from May to October 2023. The data used in this research was primary data obtained based on questionnaires and secondary data from various online media. The sampling method is by chance (accidental sampling). The sampling method used was random (random sampling). The number of respondents was 100 people using sample calculations, namely the Slovin formula, producing 50 respondents. The data analysis used is chi square analysis with the help of SPSS statistics. The results of the chi square analysis show that for all consumer preference variables regarding purchasing flower arrangements at the Quinn Florist shop in Winangun Dua Village, Malalayang District, Manado City, there are differences in consumer preferences for flower arrangements. The research results show that the price, quality, promotions and service are the same, but differ in the type and consumer preferences for purchasing flower arrangements at the Quinn Florist shop in Winangun Dua Village, Malalayang District, Manado City, namely flower arrangements at a price of IDR35,000 to IDR150,000, the type of series is pot/table, the quality is seen from the beauty, promos namely discounts, and fast responsive service.